Ação de fungicidas e acibenzolar-se-methyl no controle da pinta preta do tomateiro - Tofoli, Jesus Guerino [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
O presente trabalho visou verificar a ação “in vitro” e “in vivo” de alguns fungicidas e do indutor de resistência acibenzolar-S-methyl (BTH) no controle da pinta preta do tomateiro e seus reflexos na produção. A ação “in vitro” de fungicidas, nas concentrações de 0, 1, 10 e 100 μgmL-1 do ingrediente ativo, foi verificada com base no crescimento micelial, germinação de conídios e efeito anti-esporulante sobre A. solani. Em condições de casa de vegetação foram estudadas as ações: preventiva, residual e curativa de fungicidas em cultivares com diferentes níveis de resistência a pinta preta. Em experimentos de campo, realizados nos municípios paulistas de Sumaré (1999), Socorro (2000) e Bragança Paulista (2000 e 2001), foi avaliada a ação de diferentes grupos fungicidas e acibenzolar-S-methyl (isolado, em mistura com fungicidas e em programas de aplicação) sobre: a severidade da doença (folíolos e hastes); redução de área foliar; incidência de frutos sadios; doentes e danificados pelo sol; massa fresca de frutos sadios, produção em kilos por 10 plantas e porcentagem de frutos grandes, médios e pequenos (Bragança Paulista, 2001). Todos os fungicidas apresentaram ação positiva e diferenciada para todos os parâmetros avaliados, em função das características inerentes de cada princípio ativo. Os maiores potenciais de controle foram verificados para os fungicidas com maior especificidade e ação sistêmica... .

The aim of this study was to verify the “in-vitro” and in-vivo effectiveness of various fungicides and plant activator acibenzolar-S-methyl (BTH) in the control of tomato early blight and its effects on yield. The in-vitro effect of the fungicides, in the concentrations 0, 1, 10 and 100 μgmL-1 of the active ingredient, was assessed based on mycelial growth, conidial germination, and the antisporulating effect on A. solani. The various groups of fungicides were studied to compare their preventative, residual and curative efficacy, in greenhouse environment. Field tests were conducted in the state of São Paulo, Brazil, in the countries of Sumaré (1999), Socorro (2000) and Bragança Paulista (2000 and 2001), to compare the effect of various fungicide groups and acibenzolar-S-methyl (alone, mixed with the fungicides, or applied in conjunction with fungicidal treatments) on various parameters: the severity of the disease (leaflets and stems); percentage of leaf drop; relative numbers of healthy fruit as compared to diseased or sun-damaged fruit; yield in kg per 10 plants; and the relative percentages of large, medium and small-sized fruits (Bragança Paulista, 2001). All the fungicides presented a positive effect on all of the parameters evaluated, consistent with the active ingredients of each. The greatest efficacies of control were shown by systemic, more-specific fungicides. In regard to mycelial growth and conidial germination, the greatest inhibition percentages were obtained with metconazole, tebuconazole, difenoconazole, iprodione, cyprodinil, procymidone, prochloraz, fluazinam and pyrimethanil. The fungicides kresoxim methyl, azoxystrobin, pyraclostrobin+methiram, fenamidone+chlorothalonil and famoxadone+mancozeb presented an intermediate degree of inhibition on the mycelial growth and complete inhibition of conidial germination at concentrations of 1 μgmL-1 and above... (Complete abstract, click electronic address below).
Keywords: Tomate; Alternaria solani; Fungicidas in vitro; Fungicidas in vivo